The application of time planning and monitoring techniques in Malaysia construction industry / Anis Azlina Ahmad Fuad - Ahmad Fuad, Anis Azlina (2002)
In writing this project dissertation, I am prompted to write on the topic of "The Application of Time Planning and Monitoring Techniques in Malaysia Construction Industry" This is because I always felt that the success of a project is very much depending on a proper management skill and planning techniques used. Among the various planning techniques, time planning and monitoring techniques are used by most of the contractors in the construction industry but very often these techniques are used for "show" only. This is especially true amongst the "small" contractor in Malaysia construction industry. Bar chart are drawn for the mere purposed to comply with the contract requirement and very often the programme is not updated to suit the latest development or progress on site.